PERSPEKTIF SANTRI TAHFIDZ MAMBAUSH SHOLIHIN GRESIK TENTANG KH. KHOLIL BANGKALAN MADURA - Nur Faizin; Abduloh Safik; Najwatul Ummah; Nur Maulidah (Hikmah: Journal of Islamic Studies, 2022)
AbstractThis paper is a report from research on how the views of santri tahfidz Mambaus Sholihin (MBS) Gresik towards KH. Kholil Bangkalan, where he is known as a prominent cleric, charismatic, and has many karomah. This research also aims to avoid the journey of his life by knowing his biography, reviewing the stories related to him. This research aims to find out several things of the privileges possessed by him when he was still taking part in spreading Islamic teachings. In this research, the researchers use a qualitative approach where the technique of data collection uses how to collect data through websites and scientific papers related to KH. Muhammad Kholil and written interviews to several students of Tahfidz MBS and surrounding areas who memorized the Quran. As for the analysis of the data, the researchers use qualitative-descriptive analysis that combines to analyze or explain the writing of various data collected in the form of written survey results and from scientific works that have been published. Abstrak Artikel ini merupakan laporan dari peneltian tentang pandangan santri tahfidz Mambaus Sholihin (MBS) Gresik terhadap KH. Kholil Bangkalan. Beliau dikenal sebagai seorang ulama terpandang, karismatik, dan memiliki banyak karomah. Penelitian ini bertujuan untuk napak tilas perjalanan hidup beliau dengan cara mengetahui biografi, menelaah kembali cerita-cerita yang berhubungan dengan beliau, juga untuk mengetahui beberapa keistimewaan yang dimiliki oleh beliau ketika masih berkiprah menyebarkan ajaran Islam. Penelitian ini menggunakan pendekatan kualitatif dimana teknik pengumpulan datanya menggunakan cara mengumpulkan data lewat website dan karya ilmiah yang terkait dengan KH. Muhammad Kholil dan interview tertulis kepada beberapa santri Tahfidz MBS dan sekitarnya yang menghafal Al-Quran. Sedangkan untuk analisis datanya menggunakan analisis deskriptif kualitatif yang berfugsi untuk menganalisis atau memberi penjelasan tentang tulisan dari berbagai data yang dikumpulkan berupa hasil survey tertulis dan dari karya ilmiah yang sudah dipublikasikan.